Providentia Dei Dalam Penanaman dan Pertumbuhan Gereja - Hia, Vivian Vian; Liem, Stephanus (Jurnal Lentera Nusantara, 2023)
This article examines providentia Dei in the lives of believers which manifests in church planting and growth. God is faithful and loving to each of His people because man is a precious creation. God creates according to His will and in His will He also participates in maintaining the creation because He is not a lazy God (deus otiosus), but He is a God who always participates in the growth of each of His people. The method used in this research is the literature study method. Literature study as a way of tracing and collecting data and then analyzing it, the author also identifies other theories systematically, and uses Bible verses that support the discussion and journals related to the topic of discussion. The results show that God is always at work in every aspect of His people's lives. It is only humans who often assume the absence of God's providence because they only focus on the suffering experienced instead of gratitude and hope in God.AbstrakArtikel ini mengkaji tentang providentia Dei di dalam kehidupan orang percaya yang berwujud dalam penanaman dan pertumbuhan gereja. Allah setia dan penuh kasih kepada setiap umat-Nya karena manusia adalah ciptaan yang berharga. Allah mencipta seturut dengan kehendak-Nya dan dalam kehendak-Nya tersebut Ia juga turut ikut memelihara ciptaan tersebut karena Ia bukan Allah yang pemalas (deus otiosus), melainkan Ia adalah Allah yang selalu turut ikut serta dalam pertumbuhan setiap umat-Nya. Metode yang digunakan dalam penelitian ini adalah metode studi literatur atau pustaka. Hasil penelitian menunjukan bahwa Allah selalu turut bekerja dalam setiap aspek kehidupan umat-Nya. Tidak sekalipun Allah membiarkan umat-Nya berjalan sendirian, hanya saja manusia yang seringkali menganggap ketidak adanya pemeliharaan Allah karena mereka hanya fokus pada penderitaan yang dialami bukan pada rasa ucapan syukur dan pengharapan didalam Allah.